Towards a Fully Integrated sub-THz MicrofluidicSensor Platform for Dielectric Spectroscopy - Carl Heine; Emre Can Durmaz; Defu Wang; Zhibo Wang; Matthias Wietstruck; Bernd Tillack; Dietmar Kissinger (Frequenz, 2022)
Dielectric spectroscopy in the sub-THz regime is a promising candidate for microfluidic-based analysis of biological cells and bio-molecules, since multiple vibrational and rotational transition energy levels exist in this frequency range (P. Siegel, “Terahertz technology in biology and medicine,” IEEE Trans. Microw. Theor. Tech., vol. 52, pp. 2438–2447, 2004). This article presents our recent efforts in the implementation of microfluidic channel networks with silicon-based technologies to unleash the potential of an integrated sub-THz microfluidic sensor platform. Various aspects of dielectric sensors, readout systems, flowmeter design as well as implemention- and technology-related questions are addressed. Three dielectric sensor systems are presented operating at 240 GHz realizing transmission-based, reflection-based and full two-port architectures. Furthermore different silicon based microchannel integration techniques are discussed as well as a novel copper pillar-based PCB microchannel method is proposed and successfully demonstrated.